Macedonia - Moving to Faster and More Inclusive Growth A Country Economic Memorandum : Main Report and Annex - World Bank (World Bank, 2012)
This report deals with medium and long-term growth issues rather than the challenges posed by the world financial crisis, the structural policy options presented in the report become even more important in that context, and can help to partially mitigate the impact of the crisis on Macedonia. Section B looks at poverty and inequality issues. Section C examines Macedonia's past growth in terms of total factor productivity analysis, drawing the connection with labor and capital, and within these broad factors, human capital and infrastructure. It also compares Macedonia's growth to a successful regional comparator, Slovakia. Section D benchmarks Macedonia's performance in important policy areas that could affect growth relative to comparator countries. It also estimates how much improved performance in these areas could raise potential growth. Section E looks at efficiency in public expenditure and public investment important issues in raising growth. Section F summarizes these analyses and makes some initial recommendations.